Relación entre la desconexión moral y el ciberbullying en estudiantes de secundaria - Barbarán Miranda, Vanessa Lisette (2024)
Cyberbullying is a problem that affects the psychological environment of the adolescent, referring to aggressive, repetitive and intentional behavior directed to another, through digital media, so it is important to analyze the factors that influence it. The objective of this research is to identify the relationship between moral disengagement and cyberbullying in secondary school students, through a review process of quantitative research articles in the last 6 years. The PRISMA guide was used to guide the methodology. The article search was performed in the Scopus, Web of Science, ScienceDirect and Springerlink databases, in which a total of 352 studies were identified and considering the detailed inclusion and exclusion criteria, 11 were chosen. The results indicated that there is a positive relationship between moral disconnection and cyberbullying in high school students. From this, recommendations are proposed from the role of the psychologist in his intervention with the different educational agents.